Factors associated with bone mineral density in healthy African women. Issue 1 (December 2015) - Mgodi, Nyaradzo; Kelly, Cliff; Gati, Brenda; Greenspan, Susan; Dai, James; Bragg, Vivian; Livant, Edward; Piper, Jeanna; Nakabiito, Clemensia; Magure, Tsitsi; Marrazzo, Jeanne; Chirenje, Z.; et al.
Abstract Summary There is a paucity of normative bone mineral density (BMD) data in healthy African women. Baseline total hip and lumbar spine BMD was measured in premenopausal women. BMD distribution was comparable to that of a reference population and was impacted by several factors including contraception and duration of lactation. Introduction Normative data on bone mineral density (BMD) and the cumulative impact of lactation, contraceptive use, and other factors on BMD in healthy African women have not been well studied. Objectives The objective of this study was to determine the factors associated with BMD in healthy premenopausal women in Uganda and Zimbabwe. Methods Baseline total hip (TH) and lumbar spine (LS) BMD was measured by dual x-ray absorptiometry in 518 healthy, premenopausal black women enrolling in VOICE, an HIV-1 chemoprevention trial, at sites in Uganda and Zimbabwe. Contraceptive and lactation histories, physical activity assessment, calcium intake, and serum vitamin D levels were assessed. Independent factors associated with BMD were identified using an analysis of covariance model. Results The study enrolled 331 women from Zimbabwe and 187 women from Uganda. Median age was 29 years (IQR 25, 32) and median body mass index (BMI) was 24.8 kg/m2 (IQR 22.2, 28.6). In univariate analyses, lower TH BMD values were associated with residence in Uganda (p  < 0.001), lower BMI (p  < 0.001), and any use of and duration of depot-medroxyprogresterone acetate. Use of oral contraceptives, progestin-only implants, and higher physical activity levels were protective against reduced BMD. Similarly, lower LS BMD values were associated with these same factors but also higher parity and history of breastfeeding. In a multivariable analysis, lower TH and LS BMD values were associated with enrollment in Uganda, lower BMI, and lower physical activity level; contraceptive use was associated with lower spine BMD, and breastfeeding contributed to lower total hip BMD. Conclusions Among healthy premenopausal women, TH and LS BMD was higher in Zimbabwe than Uganda. Additional factors independently associated with BMD included BMI, physical activity level, contraceptive use, and lactation.